Negative electrode sheet, secondary battery, battery module, battery pack, and power consuming device

The negative electrode sheet for sodium-ion batteries addresses energy and material limitations by optimizing active material parameters, resulting in improved energy density and cycle performance through enhanced ion transmission and compaction.

JP2025502239AActive Publication Date: 2025-01-24CONTEMPORARY AMPEREX TECHNOLOGY (HONG KONG) LIMITED
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024541915
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2022-07-14
Publication Date
2025-01-24
Estimated Expiration
2042-07-14

AI Technical Summary

Technical Problem

Lithium-ion batteries face challenges due to high costs and resource depletion, while sodium-ion batteries have lower energy density and performance limitations, necessitating improvements in material restrictions and voltage platforms to enhance their commercial viability.

Method used

A negative electrode sheet for sodium-ion batteries is designed with specific parameters for active material particles, including tap density, median diameter differences, and porosity to improve energy and capacity performance, utilizing hard carbon particles with controlled diameters and shapes to enhance compaction density and ion transmission.

Benefits of technology

The solution results in sodium-ion batteries with higher energy density, lower impedance, and improved cycle performance by ensuring effective adsorption and desorption of sodium ions, maintaining high compaction density without distortion, and enhancing electron and ion transmission.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025502239000001_ABST
    Figure 2025502239000001_ABST
Patent Text Reader

Abstract

The present application provides a negative electrode sheet, a secondary battery, a battery module, a battery pack, and a power consuming device. The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer located on at least one surface of the negative electrode current collector, the negative electrode film layer includes first negative electrode active material particles and second negative electrode active material particles, the first negative electrode active material particles include a plurality of adsorption holes, and the first negative electrode active material particles have a tap density of 0.4 g / cm. 3 ~1.4g / cm 3 where the difference d between the median diameters of the first negative electrode active material particles and the second negative electrode active material particles satisfies 3 μm≦d≦19 μm, and the compaction density PD of the negative electrode film layer is 0.8 g / cm 3 ≦PD≦1.4g / cm 3 Meet the following.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present application relates to the technical field of batteries, and in particular to a negative electrode sheet, a secondary battery, a battery module, a battery pack, and a power consuming device. [Background technology]

[0002] With the daily emergence of energy and environmental problems, new energy industries are attracting more and more attention. Lithium-ion batteries have been widely used as important new energy storage devices in recent years due to their characteristics such as high energy density and good cycle performance. However, the active material resources related to lithium-ion batteries are scarce, the cost of batteries remains high, and serious problems such as the depletion of related resources are faced, so the development of other low-cost metal-ion secondary battery systems is required.

[0003] Sodium ion batteries have the advantages of low cost, abundant resources, and similar manufacturing process to lithium ion batteries, and have therefore become a popular research direction in recent years.

[0004] However, due to the low capacity per gram of the current positive and negative electrode materials of sodium-ion batteries and the limitations of the voltage platform, the energy density of sodium-ion batteries is always far behind that of lithium-ion batteries, making it impossible to realize practical commercial applications. In addition, the initial coulombic efficiency and multiplier performance of sodium-ion batteries also need to be improved. Summary of the Invention

[0005] The present application has been made in consideration of the above-mentioned problems, and aims to provide a negative electrode sheet, a secondary battery, a battery module, a battery pack, and a power consuming device that can effectively improve the energy density and multiplication performance of a sodium ion battery.

[0006] A first aspect of the present application relates to a negative electrode current collector and a negative electrode film layer located on at least one surface of the negative electrode current collector, the negative electrode film layer including first negative electrode active material particles and second negative electrode active material particles, the first negative electrode active material particles including a plurality of adsorption holes, and the tap density of the first negative electrode active material particles is 0.4 g / cm 3 ~1.4g / cm 3 and can be selected from 0.6g / cm 3 ~1.0g / cm 3 a negative electrode film layer having a median diameter difference d between the first negative electrode active material particles and the second negative electrode active material particles satisfying 3 μm≦d≦19 μm, and a compaction density PD of the negative electrode film layer is 0.8 g / cm 3 ≦PD≦1.4g / cm 3 , selectable, 1.0g / cm 3 ≦PD≦1.2g / cm 3 To provide a negative electrode sheet that satisfies the above requirements.

[0007] As a result, the present application can provide a high porosity inside the negative electrode film layer while providing a high compaction density in the negative electrode film layer by blending the first negative electrode active material particles and the second negative electrode active material particles that satisfy the above conditions. Specifically, the first negative electrode active material particles include a plurality of adsorption holes, and the tap density is within the above appropriate range, so that even when cold pressed, the first negative electrode active material particles can have a sufficient number of adsorption holes inside. As a result, Na + is smoothly adsorbed to the first negative electrode active material particles during charging, and is smoothly detached during discharging. Furthermore, when the difference between the median diameter of the first negative electrode active material particles and the median diameter of the second negative electrode active material particles is within the above appropriate range, it is advantageous for the second negative electrode active material particles to be filled into the gaps between the multiple first negative electrode active material particles, so that the negative electrode active material particles have a high bulk density, and the negative electrode film layer after cold pressing has an appropriate compaction density. As a result, the negative electrode active material particles in the negative electrode film layer are in close contact with each other, thereby improving the transmission performance of electrons and sodium ions in the negative electrode sheet, and further improving the multiplication performance of the sodium ion battery.

[0008] In any embodiment, the median diameter D of the first negative electrode active material particles 1 50 is 4 μm to 50 μm, optionally 4 μm to 25 μm, and the median diameter D of the second negative electrode active material particles 2 50 is between 1 μm and 40 μm, and optionally between 1 μm and 20 μm.

[0009] D 1 50, D 2 50 is within the appropriate range, on the other hand, D 1 50 and D 2 50 is advantageous to control that the difference between the first and second negative electrode active material particles is within the range specified in the present application, which is advantageous for the second negative electrode active material particles to be filled into the gaps between the first negative electrode active material particles, and is further advantageous for improving the compaction degree of the negative electrode film layer, and on the other hand, the first negative electrode active material particles and the second negative electrode active material particles can have good electron and sodium ion transmission performance inside the particles, as well as the first negative electrode active material particles and the second negative electrode active material particles can have low particle interface resistance. As a result, when the negative electrode sheet of the present application is applied to a sodium ion battery, it allows the sodium ion battery to have high energy density and low impedance, and the sodium ion battery can have high capacity, good multiplication performance and cycle performance.

[0010] In any embodiment, the mass percentage content of the first negative electrode active material particles relative to the total mass of the first negative electrode active material particles and the second negative electrode active material particles is 5% to 95%, and optionally 70% to 95%.

[0011] When the mass percentage content of the first negative electrode active material particles and the second negative electrode active material particles is within the above suitable range, the second negative electrode active material particles can be ensured to fill the voids of the first negative electrode active material particles, while the negative electrode active material particles can have a suitable specific surface area, thereby improving the compaction degree of the negative electrode membrane layer, improving the contact area between particles, improving the transmission path between particles, and avoiding the occurrence of break bridges between particles, so that the sodium ion battery can have high energy density and cycle performance.

[0012] In any embodiment, the elongation percentage E of the negative electrode sheet satisfies 0.1%≦E≦0.2%, selectably 0.1%≦E≦0.15%.

[0013] When the difference in median diameter between the first and second negative active material particles of the present application is within a suitable range, the negative active material particles can have a high bulk density, and therefore, compared with negative active material particles having a low bulk density, the negative sheet of the present application can have a lower elongation rate under the same cold pressing parameters.

[0014] In any embodiment, the coating weight CW of the negative electrode film layer on one side is 2 mg / cm 2 ~13mg / cm 2 and selectable at 5mg / cm 2 ~12mg / cm 2 It is.

[0015] When the coating weight of the negative electrode film layer on one side is within the above suitable range, it is advantageous to control the thickness of the negative electrode film layer within a suitable range. This not only allows electrons and sodium ions to have a suitable migration path in the negative electrode sheet, but also allows the negative electrode sheet to have a suitable capacity. Therefore, when the negative electrode sheet of the present application is applied to a sodium ion battery, the sodium ion battery can have good multiplication performance and high energy density.

[0016] In any embodiment, the negative electrode film layer satisfies 30%≦P≦60%, optionally 45%≦P≦55%, where P=[1-CW / (d1*PA)]*100%, d1=d2 / (1+E), CW represents the coating weight of one side of the negative electrode film layer, PA represents the true density of the negative electrode film layer on one side, E represents the elongation of the negative electrode sheet, and d2 represents the thickness of the negative electrode film layer on one side.

[0017] When the parameter P of the negative electrode film layer satisfies the above condition, the increase in the compaction degree of the negative electrode film layer is mainly achieved by the increase in the bulk density of the negative electrode active material particles, and it is believed that the porosity of the negative electrode film layer is not significantly affected, which not only improves the compaction degree of the negative electrode film layer, but also maintains the electrolyte wettability of the negative electrode film layer, and ensures that the secondary battery has high energy density and good power supply performance.

[0018] In any embodiment, the pore size of the adsorption pores in the first negative electrode active material particles is 0.1 nm to 16 nm, and optionally 1 nm to 7 nm. When the pore size distribution of the adsorption pores is within the above appropriate range, Na + This is advantageous for the adsorption and desorption of the carbon nanotube, and is also advantageous for improving the multiplication performance of the secondary battery.

[0019] Optionally, the first negative electrode active material particles have a specific surface area of ​​less than 1 m 3 / g~40m 3 / g, selectable, 1.5m 3 / g~10m 3 / g. When the specific surface area of ​​the first negative electrode active material particles is within a suitable range, the negative electrode sheet not only has good sodium ion transmission performance, but also can reduce the loss of active ions caused by the solid electrolyte interface (SEI) membrane, thereby ensuring the initial coulombic efficiency of the sodium ion battery.

[0020] Optionally, the interplanar spacing of the (002) plane of the first negative electrode active material particles is 0.34 nm to 0.45 nm, and optionally 0.35 nm to 0.4 nm. By having the interplanar spacing of the first negative electrode active material particles within an appropriate range, Na + can be smoothly inserted and removed, thereby improving the multiplication performance of the sodium ion battery.

[0021] Optionally, the first negative electrode active material particles have a true density of 1.3 g / cm 3 ~2.0g / cm 3 and selectable 1.4g / cm 3 ~1.8g / cm 3 When the true density of the first negative electrode active material particles is within the above range and the tap density is within the range defined in the present application, it is considered that the first negative electrode active material particles contain a sufficient number of adsorption holes. + can be smoothly adsorbed and desorbed, and the sodium ion battery can have good power supply performance.

[0022] In any embodiment, the first negative electrode active material particles are one or more types selected from hard carbon, soft carbon, and mesocarbon microbeads, and the second negative electrode active material particles are one or more types selected from hard carbon, soft carbon, and mesocarbon microbeads. The particle production process selected from the above types of materials is mature, and the first negative electrode active material particles and the second negative electrode active material particles that meet the conditions of the present application can be easily obtained by processing.

[0023] In either embodiment, the first negative electrode active material particles have an irregular shape and / or a microspherical shape, and the second negative electrode active material particles have an irregular shape and / or a microspherical shape.

[0024] Optionally, the mass percentage content of the first negative electrode active material particles having an irregular shape relative to the total mass of the first negative electrode active material particles and the second negative electrode active material particles is 5% to 95%, and optionally 70% to 95%.

[0025] When the difference in median diameter between the first and second negative electrode active material particles is within the range of the present application, the negative electrode membrane layer can have a high compaction degree regardless of the morphology of the first and second negative electrode active material particles, which improves the process flexibility of the negative electrode sheet and allows the sodium ion battery to have a high energy density.

[0026] In any embodiment, the first negative electrode active material particles are selected from irregularly shaped hard carbon particles, and the second negative electrode active material particles are selected from microspherical hard carbon particles, and the mass percentage content of the first negative electrode active material particles is 70% to 95% based on the total mass of the first negative electrode active material particles and the second negative electrode active material particles.

[0027] When the second negative electrode active material particles are microspherical hard carbon particles, they can not only fill the gaps between a plurality of first negative electrode active material particles, but also improve the compaction degree of the negative electrode film layer, the adhesive force of the adhesive to the negative electrode active material particles and the conductive performance of the negative electrode film layer, and can also exert a certain sliding effect to further improve the compaction degree of the negative electrode film layer. When the ratio of the first negative electrode active material particles and the second negative electrode active material particles is within a suitable range, the negative electrode active material particles have a suitable specific surface area, so that the surface of the negative electrode active material particles has a suitable amount of active sites for electrochemical reaction, and can ensure the Coulombic efficiency of the sodium ion battery.

[0028] In any embodiment, the first negative electrode active material particles are selected from microspherical hard carbon particles, and the median diameter D of the first negative electrode active material particles is 1 50 is 10 μm to 50 μm, the second negative electrode active material particles are selected from microspherical hard carbon particles, and the median diameter D of the second negative electrode active material particles is 2 50 is 5 μm to 40 μm, where the mass percentage content of the first negative electrode active material particles relative to the total mass of the first negative electrode active material particles and the second negative electrode active material particles is 5% to 95%, optionally 70% to 95%.

[0029] When the microspherical hard carbon particles themselves have a high bulk density, and the median diameters of the first and second negative electrode active material particles satisfy the above range, the bulk density of the negative electrode active material particles can be further improved. Furthermore, the microspherical second negative electrode active material particles can simultaneously exert a hole-filling function and a sliding function, thereby significantly improving the compaction degree of the negative electrode film layer. Therefore, when the negative electrode sheet of the present application is applied to a sodium ion battery, it can significantly improve the energy density, the multiplication performance, and the cycle stability of the sodium ion battery.

[0030] In any embodiment, the compaction density PD of the negative electrode film layer is 1.0 g / cm 3 ≦PD≦1.2g / cm 3 and the negative electrode film layer satisfies 30%≦P≦60%, optionally 45%≦P≦55%, where P=[1-CW / (d1*PA)]*100%, d1=d2 / (1+E), CW represents one-sided coating weight of the negative electrode film layer, PA represents the true density of the negative electrode film layer on one side, E represents the elongation rate of the negative electrode sheet, and d2 represents the thickness of the negative electrode film layer on one side.

[0031] When the parameter P of the negative electrode film layer satisfies the above condition, the increase in the compaction degree of the negative electrode film layer is believed to be mainly due to the increase in the bulk density of the negative electrode active material particles. Therefore, the hard carbon particles can provide the negative electrode film layer with a high compaction degree without distortion or slippage. This makes it possible to apply hard carbon materials to sodium ion batteries, which can have a wide range of applications.

[0032] In any embodiment, the negative electrode film layer further includes a slip-increasing component, the ratio of the mass of the slip-increasing component to the sum of the mass of the first negative electrode active material particles and the second negative electrode active material particles is 100:2 to 100:1, and the slip-increasing component includes one or more of artificial graphite, natural graphite, and graphene.

[0033] When the negative electrode film layer has a small amount of slip-increasing component, the slip-increasing component can exert a slipping effect during the cold pressing process, thereby further improving the compaction degree of the negative electrode film layer. In addition, the slip-increasing component also has good electrical conductivity, and when applied to the negative electrode sheet, it can further improve the electronic transmission performance of the negative electrode sheet.

[0034] In any embodiment, the negative electrode film layer further includes a flexible adhesive, the flexible adhesive including one or more of a styrene acrylic emulsion, a copolymer of vinylidene fluoride and tetrafluoroethylene, a copolymer of vinylidene fluoride and hexafluoropropylene, a copolymer of vinylidene fluoride and acrylic esters, polytetrafluoroethylene, nitrile rubber, and hydrogenated nitrile rubber.

[0035] The negative electrode film layer includes the flexible adhesive and has good flexibility, so that the negative electrode film layer has a smaller stress during the cold pressing process, and the negative electrode sheet has a lower elongation rate, which can further improve the compaction degree of the negative electrode film layer and improve the energy density of the sodium ion battery.

[0036] A second aspect of the present application provides a secondary battery including the negative electrode sheet of the first aspect of the present application.

[0037] The secondary battery of the present application can have high energy density and good multiplication performance by including the negative electrode sheet of the first aspect of the present application.

[0038] A third aspect of the present application provides a battery module including the secondary battery of the second aspect of the present application.

[0039] A fourth aspect of the present application provides a battery pack including the battery module of the third aspect of the present application.

[0040] A fifth aspect of the present application provides a power consuming device including at least one selected from the secondary battery of the second aspect of the present application, the battery module of the third aspect of the present application, or the battery pack of the fourth aspect of the present application.

[0041] The battery module, battery pack, and power consuming device of the present application include the secondary battery of the present application, and therefore have at least the same advantages as the secondary battery. [Brief description of the drawings]

[0042] [Figure 1] FIG. 2 is a schematic diagram of an elongation test of a negative electrode sheet according to an embodiment of the present application. [Diagram 2] FIG. 1 is a schematic diagram of a secondary battery according to an embodiment of the present application. [Diagram 3] FIG. 3 is an exploded view of the secondary battery according to the embodiment of the present application shown in FIG. 2. [Figure 4] FIG. 1 is a schematic diagram of a battery module according to an embodiment of the present application. [Diagram 5] FIG. 1 is a schematic diagram of a battery pack according to an embodiment of the present application. [Figure 6] FIG. 6 is an exploded view of the battery pack according to the embodiment of the present application shown in FIG. 5. [Figure 7] 1 is a schematic diagram of a power consuming device that uses a secondary battery as a power source according to an embodiment of the present application. [Figure 8] 1 is a scanning electron microscope photograph (SEM image) of the negative electrode sheet according to Example 1 of the present application. Reference numerals: 1 battery pack, 2 upper housing, 3 lower housing, 4 battery module, 5 secondary battery, 51 case, 52 electrode assembly, 53 cover plate DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0043] Hereinafter, the embodiments specifically disclosing the negative electrode sheet, secondary battery, battery module, battery pack, and power consumption device of the present application will be described in detail with reference to the drawings as appropriate. However, unnecessary detailed description may be omitted. For example, detailed description of well-known matters and duplicated description of substantially the same configuration may be omitted. This is to avoid the following description becoming unnecessarily redundant and to make it easy for those skilled in the art to understand. Note that the attached drawings and the following description are provided to enable those skilled in the art to fully understand the present application, and are not intended to limit the subject matter described in the claims.

[0044] The "ranges" disclosed in this application are defined in the form of lower and upper limits, and a given range is defined by selecting one lower limit and one upper limit, and the selected lower and upper limits define the boundaries of the particular range. Such defined ranges may be inclusive or exclusive of the end values, and may be arbitrarily combined, i.e., any lower limit may be combined with any upper limit to form a range. For example, if the ranges 60-120 and 80-110 are recited for a particular parameter, it is understood that the ranges 60-110 and 80-120 are also contemplated. In addition, if the minimum range values ​​1 and 2 and the maximum range values ​​3, 4, and 5 are recited, the following ranges may all be contemplated: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "a-b" is an abbreviation for any combination of real numbers between a and b, where a and b are both real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" are listed herein, with "0-5" being an abbreviation for combinations of these numerical values. Furthermore, expressing a parameter as an integer of 2 or greater is equivalent to disclosing that the parameter is, for example, the integers 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0045] Unless otherwise specified, all embodiments and optional embodiments in the present application may be combined with each other to form a new technical solution.

[0046] Unless otherwise specified, all technical features and optional technical features of the present application may be combined with each other to form a new technical solution.

[0047] Unless otherwise stated, all steps in the present application may be performed in sequence, may be performed randomly, and are preferably performed in sequence. For example, when the method includes steps (a) and (b), it means that the method may include steps (a) and (b) performed in sequence, or may include steps (b) and (a) performed in sequence. For example, when the method may further include step (c), it means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), may include steps (a), (c), and (b), or may further include steps (c), (a), and (b), etc.

[0048] Unless otherwise stated, the terms "having," "comprising," and "including" referred to in this application may be open ended or closed ended. For example, the terms "having," "comprising," and "including" indicate that the term may further comprise, comprise, or include other components not listed, or may only comprise or include the listed components.

[0049] Unless otherwise stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist), A is false (or does not exist) and B is true (or exists), or A and B are both true (or exist).

[0050] In order to improve the energy density and multiplier performance of a sodium ion battery, it is important to select the negative electrode active material of the sodium ion battery.

[0051] As a result of intensive research, the inventors have found that, unlike the lithium insertion reaction of lithium ion batteries, the negative electrode of a sodium ion battery undergoes a charging process in which Na + Not only does the intercalation of Na occur in the negative electrode active material, + By selecting negative electrode active material particles with multiple adsorption holes, it was found that Na adsorption also occurs during the long-term cycle process. + It has been found that the negative electrode can be smoothly inserted and removed from the negative electrode, and the capacity of the negative electrode can be ensured. However, after the negative electrode active material particles having a plurality of adsorption holes are prepared into the negative electrode membrane layer, the compaction density of the negative electrode membrane layer is low, which not only affects the energy density of the sodium ion battery, but also leads to the transmission path of electrons and sodium ions in the negative electrode sheet being long, thereby reducing the transmission performance of electrons and sodium ions in the negative electrode sheet, and further worsening the multiplication performance of the sodium ion battery.

[0052] Based on this, the inventors have conducted extensive research and a large number of experiments to propose a negative electrode sheet, a secondary battery, a battery module, a battery pack and a power consuming device.

[0053] Negative electrode sheet

[0054] A first aspect of the present application provides a negative electrode sheet including a negative electrode current collector and a negative electrode film layer. The negative electrode film layer is located on at least one surface of the negative electrode current collector, the negative electrode film layer including first negative electrode active material particles and second negative electrode active material particles, the first negative electrode active material particles including a plurality of adsorption holes, and the first negative electrode active material particles having a tap density of 0.4 g / cm. 3 ~1.4g / cm 3 and selectable, 0.6g / cm 3 ~1.0g / cm 3Here, the difference d between the median diameters of the first negative electrode active material particles and the second negative electrode active material particles satisfies the relationship 3 μm≦d≦19 μm, 3 μm≦d≦15 μm, 3 μm≦d≦10 μm, 3 μm≦d≦5 μm, 5 μm≦d≦19 μm, 5 μm≦d≦15 μm, 5 μm≦d≦10 μm, 10 μm≦d≦19 μm, 10 μm≦d≦15 μm, or 15 μm≦d≦19 μm. The compaction density PD of the negative electrode film layer is 0.8 g / cm 3 ≦PD≦1.4g / cm 3 , 0.8g / cm 3 ≦PD≦1.2g / cm 3 , 0.8g / cm 3 ≦PD≦1.0g / cm 3 , 1.0g / cm 3 ≦PD≦1.4g / cm 3 , or 1.0 g / cm 3 ≦PD≦1.2g / cm 3 Meet the following.

[0055] Although the mechanism is not clear, the inventor of the present application unexpectedly discovered that the negative electrode membrane layer of the present application contains the first negative electrode active material particles and the second negative electrode active material particles that satisfy the above conditions, and by mixing the two kinds of negative electrode active material particles, the negative electrode membrane layer has a high compaction density and at the same time has a high porosity inside the negative electrode membrane layer. Therefore, when the negative electrode sheet of the present application is applied to a sodium ion battery, the sodium ion battery can have a high energy density and good magnification performance.

[0056] Specifically, without being limited to any theory or interpretation, the first negative electrode active material particles have a plurality of adsorption holes, and the tap density is within the above-mentioned appropriate range, so that even if the first negative electrode active material particles are cold pressed, they can have a sufficient number of adsorption holes inside. As a result, Na +is smoothly adsorbed to the first negative electrode active material particles during charging, and is smoothly detached during discharging. Furthermore, when the difference between the median diameter of the first negative electrode active material particles and the median diameter of the second negative electrode active material particles is within the above appropriate range, it is advantageous for the second negative electrode active material particles to be filled into the gaps between the multiple first negative electrode active material particles, so that the negative electrode active material particles have a high bulk density, and the negative electrode film layer after cold pressing has an appropriate compaction density. As a result, the negative electrode active material particles in the negative electrode film layer are in close contact with each other, thereby improving the transmission performance of electrons and sodium ions in the negative electrode sheet, and further improving the multiplication performance of the sodium ion battery.

[0057] In some embodiments, the median diameter D of the first negative electrode active material particles 1 50 may be 4 μm to 50 μm, and optionally is 4 μm to 25 μm, and the median diameter D of the second negative electrode active material particles 2 50 may be 1 μm to 40 μm, and is optionally 1 μm to 20 μm. For example, D 1 50 may be 4 μm, 8 μm, 10 μm, 15 μm, 20 μm, 25 μm, 35 μm, 45 μm, 50 μm, or any of the above values ​​in a range, and D 2 50 may be 1 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, or a range of any of the preceding values.

[0058] Without being limited to any theory or interpretation, 1 50, D 2 When D 50 is in the above appropriate range, it is advantageous not only for improving the compaction degree of the negative electrode film layer, but also for improving the contact between particles and reducing the impedance of the sodium ion battery. 1 50, D 2 If 50 is within the appropriate range above, D 1 50 and D 250 is advantageous to control that the difference between the first and second negative electrode active material particles is within the range specified in the present application, which is advantageous for the second negative electrode active material particles to be filled into the gaps between the first negative electrode active material particles, and further advantageous for improving the compaction degree of the negative electrode film layer; on the other hand, the first negative electrode active material particles and the second negative electrode active material particles have an appropriate particle size, which not only allows the first negative electrode active material particles and the second negative electrode active material particles to have good electron and sodium ion transmission performance inside the particles, but also allows the first negative electrode active material particles and the second negative electrode active material particles to have low particle interface resistance. As a result, when the negative electrode sheet of the present application is applied to a sodium ion battery, it allows the sodium ion battery to have high energy density and low impedance, and the sodium ion battery to have high capacity, good multiplication performance and cycle performance.

[0059] In some embodiments, the mass percentage content of the first negative electrode active material particles relative to the total mass of the first negative electrode active material particles and the second negative electrode active material particles may be 5% to 95%, and optionally 70% to 95%. For example, the mass percentage content of the first negative electrode active material particles relative to the total mass of the first negative electrode active material particles and the second negative electrode active material particles may be 5%, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 75%, 80%, 85%, 90%, 95%, or any range of the above values.

[0060] Without being limited to any theory or interpretation, when the mass percentage content of the first negative electrode active material particles and the second negative electrode active material particles is within the above suitable range, the second negative electrode active material particles can be ensured to fill the voids of the first negative electrode active material particles, while the negative electrode active material particles can have a suitable specific surface area, thereby improving the compaction density of the negative electrode membrane layer, improving the contact area between particles, improving the transmission path between particles, and avoiding the occurrence of break bridges between particles, so that the sodium ion battery can have high energy density and cycle performance.

[0061] In some embodiments, the elongation percentage E of the negative electrode sheet satisfies 0.1%≦E≦0.2%, and optionally 0.1%≦E≦0.15%. For example, E may be within a range of 0.1%, 0.12%, 0.15%, 0.18%, 0.2%, or any of the above values.

[0062] Without being limited to any theory or interpretation, when the difference in median diameter between the first negative active material particles and the second negative active material particles of the present application is within a suitable range, the negative active material particles can have a high bulk density. Therefore, compared with negative active material particles with a low bulk density, the negative sheet of the present application can have a lower elongation rate under the same cold pressing parameters.

[0063] In some embodiments, the single-sided coating weight CW of the negative electrode film layer is 2 mg / cm 2 ~13mg / cm 2 may be selected to be 5 mg / cm 2 ~12mg / cm 2 For example, CW is 2 mg / cm 2 , 5 mg / cm 2 , 8 mg / cm 2 , 10mg / cm 2 , 12 mg / cm 2 , 13 mg / cm 2 Or it may be in a range of any of the above values.

[0064] The single-sided coating weight of the negative electrode membrane layer can indicate the solid content in the negative electrode slurry coated on the single-sided negative electrode membrane layer within a unit area, and the numerical value may be equal to the areal density of the single-sided negative electrode membrane layer.

[0065] Without being limited to any theory or interpretation, when the coating weight of the negative electrode film layer on one side is within the above appropriate range, it is advantageous to control the thickness of the negative electrode film layer within an appropriate range. This not only allows electrons and sodium ions to have an appropriate migration path in the negative electrode sheet, but also allows the negative electrode sheet to have an appropriate capacity. Therefore, when the negative electrode sheet of the present application is applied to a sodium ion battery, the sodium ion battery can have good multiplication performance and high energy density.

[0066] In some embodiments, the negative electrode film layer can satisfy 30%≦P≦60%. Optionally, 45%≦P≦55%.

[0067] Here, P = [1-CW / (d1*PA)]*100%, d1 = d2 / (1+E), CW is the coating weight of the negative electrode film layer on one side, PA is the true density of the negative electrode film layer on one side, and PA = 1 / (Σx i / ρ i ) where x i indicates the mass ratio of the i-th component constituting the negative electrode film layer in the negative electrode film layer, and ρ i indicates the density of the i-th type of component, E indicates the elongation of the negative electrode sheet, and d2 indicates the thickness of the one-sided negative electrode film layer.

[0068] Without being limited to any theory or interpretation, the inventors unexpectedly found that when the parameter P of the negative electrode film layer satisfies the above conditions, the increase in compaction degree of the negative electrode film layer is mainly achieved by the increase in the bulk density of the negative electrode active material particles, and does not significantly affect the porosity of the negative electrode film layer, which not only improves the compaction degree of the negative electrode film layer, but also maintains the electrolyte wettability of the negative electrode film layer, and ensures that the secondary battery has high energy density and good power supply performance.

[0069] In some embodiments, in the first negative electrode active material particles, the pore size of the adsorption pores may be 0.1 nm to 16 nm, and optionally 1 nm to 7 nm. When the pore size distribution of the adsorption pores is within the above appropriate range, Na + This is advantageous for the adsorption and desorption of the carbon nanotube, and is advantageous for improving the multiplication performance of the secondary battery.

[0070] Optionally, the first negative electrode active material particles have a specific surface area of ​​less than 1 m 3 / g~40m 3 / g, selectable 1.5m 3 / g~10m 3 / g. When the specific surface area of ​​the first negative electrode active material particles is within a suitable range, the negative electrode sheet not only has good sodium ion transmission performance, but also can reduce the loss of active ions caused by the solid electrolyte interface (SEI) membrane, thereby ensuring the initial coulombic efficiency of the sodium ion battery.

[0071] Optionally, the interplanar spacing of the (002) plane of the first negative electrode active material particles may be 0.34 nm to 0.45 nm, or alternatively, 0.35 nm to 0.4 nm. When the interplanar spacing of the first negative electrode active material particles is within an appropriate range, Na + can be smoothly inserted and removed, thereby improving the multiplication performance of the sodium ion battery.

[0072] Optionally, the first negative electrode active material particles have a true density of 1.3 g / cm 3 ~2.0g / cm 3 may be selected to be 1.4g / cm 3 ~1.8g / cm 3 When the true density of the first negative electrode active material particles is within the above range and the tap density is within the range defined in the present application, it is considered that the first negative electrode active material particles contain a sufficient number of adsorption holes. + can be smoothly adsorbed and desorbed, and the sodium ion battery can have good power supply performance.

[0073] In the present application, the materials of the first negative electrode active material particles and the second negative electrode active material particles are not limited. In some embodiments, the first negative electrode active material particles may be one or more of hard carbon, soft carbon, and mesocarbon microbeads (MCMB), and the second negative electrode active material particles may be one or more of hard carbon, soft carbon, and MCMB.

[0074] The particle production process selected from the above types of materials is mature, and the first negative electrode active material particles and the second negative electrode active material particles that meet the conditions of the present application can be easily obtained through processing.

[0075] The morphology of the first and second negative electrode active material particles is not limited in the present application. In some embodiments, the first negative electrode active material particles may have an irregular shape and / or a microspherical shape, and the second negative electrode active material particles may have an irregular shape and / or a microspherical shape.

[0076] Optionally, the mass percentage content of the first negative electrode active material particles having an irregular shape relative to the total mass of the first negative electrode active material particles and the second negative electrode active material particles may be 5% to 95%, and optionally 70% to 95%.

[0077] The morphology of the first negative electrode active material particles and the morphology of the second negative electrode active material particles may be the same or different.

[0078] In the negative electrode sheet of the present application, when the difference in median diameter between the first negative electrode active material particles and the second negative electrode active material particles is within the range of the present application, the negative electrode film layer can have a high compaction degree regardless of the morphology of the first negative electrode active material particles and the second negative electrode active material particles, which improves the process flexibility of the negative electrode sheet and allows the sodium ion battery to have a high energy density.

[0079] In some embodiments, the first negative electrode active material particles and the second negative electrode active material particles can both be hard carbon particles.

[0080] After investigation, the inventors found that hard carbon materials have low storage voltage, high capacity and good cycle stability. In addition, the sources of hard carbon materials are abundant, and the preparation process is simple. More importantly, the lattice spacing of the hard carbon particles themselves is large and porous, which is an ideal choice for the first negative electrode active material particles of the present application. Ordinary hard carbon materials themselves have high hardness, and little distortion and slippage occur during the cold pressing process. When applied to the negative electrode film layer, the compaction degree of the negative electrode film layer is usually low, but in the negative electrode film layer of the present application, the second negative electrode active material particles with a small particle size can fill the voids of the first negative electrode active material particles, so that the first negative electrode active material particles do not need to be deformed, and the negative electrode film layer can also have a high compaction degree. Therefore, when the first negative electrode active material particles and the second negative electrode active material particles are both hard carbon particles, when the negative electrode sheet of the present application is applied to a sodium ion battery, it can reduce the cost of the sodium ion battery and improve the energy density, multiplication performance and cycle stability of the sodium ion battery.

[0081] In some embodiments, the first negative electrode active material particles may be selected from irregularly shaped hard carbon particles, the second negative electrode active material particles may be selected from microspherical hard carbon particles, and the mass percentage content of the first negative electrode active material particles may be 70% to 95% relative to the total mass of the first negative electrode active material particles and the second negative electrode active material particles.

[0082] Without being limited to any theory or interpretation, when the second negative electrode active material particles are microspherical hard carbon particles, they can not only fill the gaps between a plurality of first negative electrode active material particles, but also improve the compaction degree of the negative electrode film layer, the adhesive force of the adhesive to the negative electrode active material particles and the conductive performance of the negative electrode film layer, and can also exert a certain sliding effect to further improve the compaction degree of the negative electrode film layer. When the ratio of the first negative electrode active material particles to the second negative electrode active material particles is within a suitable range, the negative electrode active material particles have a suitable specific surface area, so that the surface of the negative electrode active material particles has a suitable amount of active sites for electrochemical reaction, and can ensure the Coulombic efficiency of the sodium ion battery.

[0083] In some embodiments, the first negative electrode active material particles are selected from microspherical hard carbon particles, and the median diameter D 1 50 is 10 μm to 50 μm, the second negative electrode active material particles are selected from microspherical hard carbon particles, and the median diameter D of the second negative electrode active material particles is 2 50 is 5 μm to 40 μm, where the mass percentage content of the first negative electrode active material particles relative to the total mass of the first negative electrode active material particles and the second negative electrode active material particles may be 5% to 95%, and optionally 70% to 95%.

[0084] Without being limited to any theory or interpretation, when the microspherical hard carbon particles themselves have a high bulk density and the median diameters of the first and second negative electrode active material particles satisfy the above range, the bulk density of the negative electrode active material particles can be further improved. Furthermore, the microspherical second negative electrode active material particles can simultaneously exert a hole filling function and a sliding function, thereby significantly improving the compaction degree of the negative electrode film layer. Therefore, when the negative electrode sheet of the present application is applied to a sodium ion battery, it can significantly improve the energy density, multiplication performance, and cycle stability of the sodium ion battery.

[0085] In some embodiments, the first negative electrode active material particles and the second negative electrode active material particles may both be hard carbon particles. The density of compaction PD of the negative electrode film layer is 1.0 g / cm 3 ≦PD≦1.2g / cm 3 and the negative electrode film layer can satisfy 30%≦P≦60%, and optionally 45%≦P≦55%, where P=[1-CW / (d1*PA)]*100%, d1=d2 / (1+E), CW represents the coating weight of one side of the negative electrode film layer, PA represents the true density of one side of the negative electrode film layer, and PA=1 / (Σx i / ρ i ) where x i indicates the mass ratio of the i-th component constituting the negative electrode film layer in the negative electrode film layer, and ρ i indicates the density of the i-th type of component, E indicates the elongation of the negative electrode sheet, and d2 indicates the thickness of the one-sided negative electrode film layer.

[0086] Without being limited to any theory or interpretation, it is believed that when the parameter P of the negative electrode film layer satisfies the above conditions, the increase in compaction degree of the negative electrode film layer is mainly achieved by the increase in bulk density of the negative electrode active material particles. Therefore, the hard carbon particles can provide the negative electrode film layer with a high compaction degree without distortion or slippage. This makes it possible to apply hard carbon materials to sodium ion batteries, which can provide the sodium ion batteries with a wide range of application prospects.

[0087] In some embodiments, the negative electrode membrane layer may further include a slip-increasing component, and the ratio of the mass of the slip-increasing component to the sum of the mass of the first negative electrode active material particles and the second negative electrode active material particles may be 100:2 to 100:1, and the slip-increasing component may include one or more of artificial graphite, natural graphite, and graphene.

[0088] Without being limited to any theory or interpretation, it is believed that if the negative electrode film layer has a small amount of slip-increasing component, the slip-increasing component can exert a slipping effect during the cold pressing process, thereby further improving the compaction degree of the negative electrode film layer. In addition, the slip-increasing component also has good electrical conductivity, and when applied to the negative electrode sheet, it can further improve the electronic transmission performance of the negative electrode sheet.

[0089] In some embodiments, the negative electrode membrane layer may further include a flexible adhesive, the flexible adhesive including one or more of styrene acrylic emulsion, copolymer of vinylidene fluoride and tetrafluoroethylene, copolymer of vinylidene fluoride and hexafluoropropylene, copolymer of vinylidene fluoride and acrylic esters, polytetrafluoroethylene, nitrile rubber, and hydrogenated nitrile rubber.

[0090] Without being limited to any theory or interpretation, the negative electrode film layer includes the flexible adhesive and has good flexibility, so that the negative electrode film layer has a smaller stress during cold pressing, the negative electrode active material particles are more easily piled up, and the negative electrode sheet has a lower elongation rate, which can further improve the compaction degree of the negative electrode film layer and improve the energy density of the sodium ion battery.

[0091] In addition, each of the negative electrode film layer parameters in the present application refers to the parameter range of one side of the negative electrode film layer. When the negative electrode film layer is provided on both sides of the negative electrode current collector, if either one of the negative electrode film layer parameters satisfies the present application, it is considered to be within the protection range of the present application.

[0092] The first negative electrode active material particles and the second negative electrode active material particles in the present application can be obtained by various methods, including but not limited to, for example, the first negative electrode active material particles and the second negative electrode active material particles can be obtained commercially or homemade.

[0093] For example, the first and second negative electrode active material particles may be hard carbon particles having an irregular shape, and the first and second negative electrode active material particles may be produced by subjecting coconut shells to a pre-carbonization process at 300° C. and a double-roll molding machine. The process includes crushing the coconut shells after the preliminary carbonization treatment into particles having a diameter of about 2 mm using a carbonization machine, and removing impurities by sieving. The process includes heat treating the particles at 400°C to 800°C, and introducing halogen or hydrogen halide gas as necessary to remove ash and obtain particles that are easy to process by ball milling. The process includes ball milling the particles to obtain carbon particles having Dv50 = 50μm / 40μm / 25μm / 20μm / 9μm / 5μm / 3μm / 1μm. The process includes placing the particles after ball milling in an inert atmosphere, maintaining the temperature at 1150°C, carbonizing the particles after ball milling, and, if necessary, introducing acetylene gas to perform carbon coating in vapor phase growth on the particles after ball milling. This process prepares the first negative electrode active material particles and the second negative electrode active material particles having irregular shapes.

[0094] As another example, the first negative electrode active material particles and the second negative electrode active material particles may be microspherical hard carbon particles. The first negative electrode active material particles and the second negative electrode active material particles are prepared by the following steps. A step of dehydrating and carbonizing starch and / or lignin at 200°C or less to obtain pre-carbonized particles with a fixed initial shape (for example, pre-carbonized particles obtained from lignin for papermaking, potato starch, corn starch, and rice starch have Dv50 of 50 μm, 25 μm, 10 μm, and 6 μm, respectively, and have a spherical or nearly spherical shape), adding a salt or polymer dehydrating agent containing N, P, S, or a halogen, such as an ammonium salt, a phosphate, a sulfate, a sulfite, a persulfate, a halide, or a polymer of the above salt, to the starch and / or lignin as necessary, and heat-treating the pre-carbonized particles at 400 to 800°C to obtain carbonized particles that are easily pulverized by ball milling or airflow pulverization; and a step of pulverizing the carbonized particles by ball milling or airflow pulverization, and further pulverizing the carbonized particles by ball milling or airflow pulverization to obtain particles of other particle sizes close to a spherical or cullet shape (for example, potato starch carbon particles having a particle size of 25 μm) into the primary ball mill. The method includes a step of obtaining first and second negative electrode active material particles having a microspherical shape by placing the particles in an inert atmosphere and maintaining the temperature at 1150° C. to carbonize the particles after ball milling, and if necessary, introducing acetylene gas to coat the particles after ball milling in vapor phase growth, thereby preparing first and second negative electrode active material particles having a microspherical shape. The method includes a step of obtaining first and second negative electrode active material particles having a microspherical shape by placing the particles in an inert atmosphere and maintaining the temperature at 1150° C. to carbonize the particles after ball milling, and if necessary, introducing acetylene gas to coat the particles after ball milling in vapor phase growth, thereby preparing first and second negative electrode active material particles having a microspherical shape. The method includes a step of obtaining first and second negative electrode active material particles having a microspherical shape by placing the particles in an inert atmosphere and maintaining the temperature at 1150° C. to carbonize the particles after ball milling, and if necessary, introducing acetylene gas to coat the particles after ball milling in vapor phase growth, thereby preparing first and second negative electrode active material particles having a microspherical shape.

[0095] In this application, tap density has a meaning well known in the art and can be measured by methods well known in the art, for example, by using a powder tap density tester (e.g., Dandong Baite BT-310) with reference to standards GB / T5162-2006 and GB / T24533-2009.

[0096] In this application, the median diameter has a meaning well known in the art, and can refer to the particle diameter when the cumulative particle size distribution percentage of particles reaches 50%. The median diameter can be measured by a method and device known in the art. For example, it can be measured using a laser particle size analyzer (e.g., Mastersizer2000E, UK) with reference to GB / T19077-2016 particle size distribution laser diffraction method.

[0097] In this application, the compaction degree of the negative electrode film layer has a meaning well known in the art and can be measured by a method well known in the art. For example, after the negative electrode sheet is cold pressed, a press machine is used to punch out a wafer with a completely coated slurry and a wafer without a slurry, each with an area of ​​S1, which are weighed to obtain average masses W2 and W1, and are measured to obtain average thicknesses T2 and T1, and the compaction degree of the negative electrode film layer PD=(W2-W1) / (T2-T1) / S1 is obtained.

[0098] In this application, the elongation rate E of the negative electrode sheet has a meaning well known in the art and can indicate the rate of change in the length in the machine direction before and after cold pressing of the negative electrode sheet. The elongation rate E can be measured using methods and equipment known in the art. As an example, as shown in FIG. 1, take a coated and dried negative electrode sheet with a length of 2 m, select two mark points A1 and A2, the connection line of A1 and A2 is parallel to the length direction of the negative electrode sheet, and use a ruler to accurately measure the distance between the mark points A1 and A2 and denote it as L1. After cold pressing the negative electrode sheet with a certain pressure, measure the distance between A1 and A2 and denote it as L2, so that E=(L2-L1) / L1.

[0099] In this application, the coating weight of one side of the negative electrode film layer has a meaning well known in the art and can be measured by a method well known in the art. For example, after the negative electrode sheet is cold pressed, a press machine is used to punch out a wafer completely coated with the slurry and a wafer not coated with the slurry, each having an area of ​​S2, and the wafers are weighed to obtain average masses M2 and M1, and the coating weight of one side of the negative electrode sheet CW=(M2-M1) / nS2, where n indicates the number of negative electrode film layers, and when the negative electrode sheet is coated on one side, n=1, and when the negative electrode sheet is coated on both sides, n=2.

[0100] In this application, the thickness d2 of the single-sided negative electrode film layer can be measured by a micrometer. For example, after the negative electrode sheet is cold-pressed, the thickness d3 of the negative electrode sheet is measured by using a micrometer, the negative electrode film layer on the surface of the negative electrode sheet is scraped off and washed with a solvent, and then the thickness d4 of the negative electrode current collector is measured by a micrometer, and d4=(d3-d4) / n, where n indicates the number of negative electrode film layers, and when the negative electrode sheet is coated on one side, n=1, and when the negative electrode sheet is coated on both sides, n=2.

[0101] In the present application, the pore size and pore size distribution of the adsorption pores of the negative electrode material have a meaning well known in the art and can be measured by a method well known in the art, for example, by a specific surface area analyzer (e.g., Tristar II 3020M).

[0102] In the present application, the specific surface area of ​​the negative electrode active material particles has a meaning well known in the art, and can be measured by a method well known in the art. For example, the specific surface area of ​​the negative electrode active material can be measured by a nitrogen adsorption / desorption method using a specific surface area analyzer (e.g., Tristar II 3020M).

[0103] In this application, the interplanar spacing has a meaning known in the art and can be measured by methods known in the art, for example, by analyzing the negative electrode active material particles by X-ray diffraction (e.g., Equinox100).

[0104] In the present application, the true density of the negative electrode active material particles has a meaning well known in the art and can be measured by a method well known in the art, for example, using a true density tester (e.g., AccuPycII1340).

[0105] The secondary battery, battery module, battery pack, and power consuming device according to the present application will be described with reference to the drawings as appropriate.

[0106] secondary battery

[0107] A second aspect of the present application provides a secondary battery, which in some embodiments may be a sodium ion battery.

[0108] In general, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator. During the charge and discharge process of the battery, active ions shuttle between the positive electrode sheet and the negative electrode sheet to be inserted and removed. The electrolyte serves to conduct ions between the positive electrode sheet and the negative electrode sheet. The separator is provided between the positive electrode sheet and the negative electrode sheet and serves mainly to prevent short-circuiting between the positive and negative electrodes while allowing ions to pass through.

[0109] [Positive electrode sheet]

[0110] The positive electrode sheet includes a positive electrode current collector and a positive electrode membrane layer provided on at least one surface of the positive electrode current collector, the positive electrode membrane layer including the positive electrode active material of the first aspect of the present application.

[0111] As an example, the positive electrode current collector has opposite surfaces facing each other in the thickness direction thereof, and the positive electrode film layer is provided on one or both of the opposite surfaces of the positive electrode current collector.

[0112] In some embodiments, the positive electrode current collector may be a metal foil sheet or a composite current collector. For example, an aluminum foil may be used as the metal foil sheet. The composite current collector may include a polymeric material base layer and a metal layer formed on at least one surface of the polymeric material base layer. The composite current collector may be formed by forming a metal material (such as aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy) on a polymeric material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0113] In some embodiments, when the secondary battery is a sodium ion battery, the positive electrode active material may be a positive electrode active material used in sodium ion batteries that is well known in the art. As the positive electrode active material, for example, only one type may be used alone, or two or more types may be combined. Here, the positive electrode active material may be sodium iron composite oxide (NaFeO2), sodium cobalt composite oxide (NaCoO2), sodium chromium composite oxide (NaCrO2), sodium manganese composite oxide (NaMnO2), sodium nickel composite oxide (NaNiO2), sodium nickel titanium composite oxide (NaNi 1 / 2 Ti 1 / 2 O2), sodium nickel manganese composite oxide (NaNi 1 / 2 Mn 1 / 2 O2), sodium iron manganese oxide (Na 2 / 3 Fe 1 / 3 Mn 2 / 3 O2), sodium nickel cobalt manganese composite oxide (NaNi 1 / 3 Co 1 / 3 Mn 1 / 3O2), sodium iron phosphate compound (NaFePO4), sodium manganese phosphate compound (NaMnPO4), sodium cobalt phosphate compound (NaCoPO4), Prussian blue-based materials, polyanion materials (phosphates, fluorophosphates, pyrophosphates, sulfates), etc., but the present application is not limited to these materials, and other conventionally known materials that can be used as a positive electrode active material for sodium ion batteries may also be used.

[0114] In some embodiments, the positive electrode membrane layer may further include an adhesive, if necessary. For example, the adhesive may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), a terpolymer of vinylidene fluoride-tetrafluoroethylene-propylene, a terpolymer of vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene, a copolymer of tetrafluoroethylene-hexafluoropropylene, and a fluorine-containing acrylate resin.

[0115] In some embodiments, the positive electrode membrane layer may further include a conductive agent. For example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0116] In some embodiments, the positive electrode sheet can be prepared by dispersing the above-mentioned components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the adhesive, and any other components, in a solvent (e.g., N-methylpyrrolidone) to form a positive electrode slurry, and applying the positive electrode slurry to a positive electrode current collector and obtaining a positive electrode sheet after processes such as drying and cold pressing.

[0117] [Negative electrode sheet]

[0118] In the secondary battery of the present application, the negative electrode sheet includes the negative electrode sheet of the first embodiment of the present application.

[0119] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer provided on at least one surface of the negative electrode current collector, the negative electrode film layer including a negative electrode active material.

[0120] As an example, the negative electrode current collector has opposite surfaces facing each other in the thickness direction thereof, and the negative electrode film layer is provided on one or both of the opposing surfaces of the negative electrode current collector.

[0121] In some embodiments, the negative electrode current collector may be a metal foil sheet or a composite current collector. For example, copper foil or aluminum foil may be used as the metal foil sheet. The composite current collector may include a polymeric material base layer and a metal layer formed on at least one surface of the polymeric material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, silver alloy, etc.) on a polymeric material substrate (e.g., a substrate such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE)).

[0122] In some embodiments, the negative electrode membrane layer may further include a conductive agent, if necessary, which may be at least one selected from superconducting carbon, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0123] In some embodiments, the negative electrode membrane layer may further include other auxiliary agents, such as a thickening agent (eg, sodium carboxymethylcellulose (CMC-Na)), as needed.

[0124] In some embodiments, the negative electrode sheet can be prepared by dispersing the above-mentioned components for preparing the negative electrode sheet, such as the first negative electrode active material particles, the second negative electrode active material particles, an optional slip extender component, a conductive agent, an adhesive, and any other components, in a solvent (e.g., deionized water) to form a negative electrode slurry, and applying the negative electrode slurry to a negative electrode current collector, and obtaining a negative electrode sheet after processes such as drying and cold pressing.

[0125] [Electrolyte]

[0126] The electrolyte serves to conduct ions between the positive electrode sheet and the negative electrode sheet. The type of electrolyte of the present application is not particularly limited and can be selected according to needs. The electrolyte may be, for example, liquid, gel, or all solid.

[0127] In some embodiments, the electrolyte uses an electrolyte solution, the electrolyte solution including an electrolyte salt and a solvent.

[0128] In some embodiments, the electrolyte salt is one or more of NaPF6, NaClO4, NaBCl4, NaSO3CF3, and Na(CH3)C6H4SO3.

[0129] In some embodiments, the solvent may be at least one selected from ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, methyl ethyl sulfone, and diethyl sulfone.

[0130] In some embodiments, the electrolyte may further include additives as necessary. For example, the additives may include a negative electrode film-forming additive and a positive electrode film-forming additive, and may include additives that improve some performance of the battery, such as an additive that improves the overcharge performance of the battery, or an additive that improves the high temperature or low temperature performance of the battery.

[0131] [Separator]

[0132] In some embodiments, the secondary battery further includes a separator. The type of the separator of the present application is not particularly limited, and any known porous structure separator having good chemical stability and mechanical stability can be selected.

[0133] In some embodiments, the separator is made of at least one material selected from glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator may be a single-layer film or a multi-layer composite film, and is not particularly limited. When the separator is a multi-layer composite film, the materials of each layer may be the same or different, and is not particularly limited.

[0134] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator can be prepared into an electrode assembly by a winding or lamination process.

[0135] In some embodiments, the secondary battery may include an exterior case that is used to seal the electrode assembly and electrolyte.

[0136] In some embodiments, the exterior of the secondary battery may be a hard case, such as a hard plastic case, an aluminum case, a steel case, etc. The exterior of the secondary battery may be a soft package, such as a bag soft package, etc. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0137] The shape of the secondary battery of the present application is not particularly limited, and may be cylindrical, rectangular, or any other shape. For example, Fig. 2 shows a secondary battery 5 having a rectangular structure as an example.

[0138] In some embodiments, referring to FIG. 3, the exterior may include a case 51 and a cover plate 53. The case 51 includes a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate are surrounded to form a receiving cavity. The case 51 has an opening communicating with the receiving cavity, and the cover plate 53 can cover the opening to seal the receiving cavity. The positive electrode sheet, the negative electrode sheet and the separator can form an electrode assembly 52 by a winding process or a lamination process. The electrode assembly 52 is sealed in the receiving cavity. The electrolyte is infiltrated into the electrode assembly 52. ​​The number of electrode assemblies 52 included in the secondary battery 5 may be one or more, and can be selected by those skilled in the art according to specific practical needs.

[0139] Battery module and battery pack

[0140] In some embodiments, the secondary battery may be assembled into a battery module, and the number of secondary batteries included in the battery module may be one or more, and a person skilled in the art can select the specific number according to the application and capacity of the battery module.

[0141] Fig. 4 shows an example of a battery module 4. Referring to Fig. 4, in the battery module 4, the multiple secondary batteries 5 may be arranged in sequence along the longitudinal direction of the battery module 4. Of course, they may be arranged in any other manner. Furthermore, the multiple secondary batteries 5 may be fixed by fasteners.

[0142] Optionally, the battery module 4 further includes a housing having an accommodating space, and the multiple secondary batteries 5 are accommodated in the accommodating space.

[0143] In some embodiments, the battery modules may be assembled into a battery pack, and the number of battery modules included in the battery pack may be one or more, and a person skilled in the art can select the specific number according to the application and capacity of the battery pack.

[0144] 5 and 6 show an example of a battery pack 1. Referring to Fig. 5 and 6, the battery pack 1 may include a battery box and a plurality of battery modules 4 provided in the battery box. The battery box includes an upper housing 2 and a lower housing 3, and the upper housing 2 is covered by the lower housing 3 to form an enclosed space for accommodating the battery modules 4. The plurality of battery modules 4 may be arranged in the battery box in any manner.

[0145] power consumption equipment The present application further provides a power consuming device including at least one of the secondary battery, battery module, or battery pack according to the present application. The secondary battery, battery module, or battery pack may be used as a power source for the power consuming device, or may be used as an energy storage means for the power consuming device. The power consuming device may include, but is not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), trains, ships, and satellites, energy storage systems, etc.

[0146] The power consumption device can be a secondary battery, a battery module, or a battery pack, depending on the usage needs.

[0147] 7 shows an example of a power consumption device, such as a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. A battery pack or a battery module can be adopted to meet the high power and high energy density requirements of the power consumption device to the secondary battery.

[0148] Other exemplary devices may be mobile phones, tablet computers, notebook computers, etc. These devices are generally required to be thin and may employ secondary batteries as a power source.

[0149] Working Example The following examples of the present application are described. The following examples are illustrative and are merely for the purpose of interpreting the present application, and should not be understood as limitations on the present application. If no specific techniques or conditions are specified in the examples, they are carried out according to the techniques, conditions or instructions described in the literature in this field. If no manufacturer is specified for the reagents or equipment used, they are all ordinary products available on the market.

[0150] Example 1 1) Preparation of positive electrode sheet The positive electrode active material is sodium nickel manganese composite oxide (NaNi 1 / 2 Mn 1 / 2 O2), acetylene black as a conductive agent, and polyvinylidene fluoride (PVDF) as an adhesive are thoroughly mixed in a weight ratio of 92:5:3 in an appropriate amount of N-methylpyrrolidone (NMP) to form a uniform positive electrode slurry. The positive electrode slurry is then applied onto a 13 μm thick positive electrode current collector aluminum foil, dried at 100°C, and pressed to obtain a positive electrode sheet.

[0151] 2) Preparation of negative electrode sheet The negative electrode active material particles, acetylene black as a conductive agent, styrene acrylic emulsion as an adhesive, and sodium hydroxymethylcellulose (CMC-Na) as a thickener are thoroughly mixed in a weight ratio of 94:1:4:1 with an appropriate amount of deionized water to form a uniform negative electrode slurry, which is then applied to both sides of a negative electrode current collector copper foil with a thickness of 8 μm, dried at 100°C, and pressed to obtain a negative electrode sheet.

[0152] Here, the negative electrode active material particles include first negative electrode active material particles and second negative electrode active material particles, and the first negative electrode active material particles and the second negative electrode active material particles are both hard carbon particles having an irregular shape, and the median diameter D of the first negative electrode active material is 1 50 is 25 μm, and the median diameter D of the first negative electrode active material particles is 2 50 is 22 μm. The mass percentage content Q1 of the first negative electrode active material particles relative to the total mass of the negative electrode active material particles is 70%. The one-sided coating weight CW of the negative electrode sheet is 8 mg / cm 2 It is.

[0153] 3) Separator Use a polyethylene PE separator (Celgard).

[0154] 4) Preparation of electrolyte Equal volumes of ethylene carbonate (EC) and propylene carbonate (PC) are uniformly mixed to obtain an organic solvent, and then NaPF6 is uniformly dissolved in the organic solvent to obtain an electrolyte, where the concentration of NaPF6 is 1 mol / L.

[0155] 5) Preparation of the battery The positive electrode sheet, separator, and negative electrode sheet are laminated in this order, the electrolyte is added, and the resulting mixture is sealed to obtain a sodium ion battery.

[0156] Examples 2 to 14 Based on the preparation method of Example 1, 1 50, D 2 50 to prepare the sodium ion batteries of Examples 2 to 14.

[0157] Examples 15 to 22 Based on the preparation method of Example 1, 1 50, D 2 50, and Q1 are adjusted to prepare the sodium ion batteries of Examples 15 to 22.

[0158] Examples 23 to 26 Based on the preparation method of Example 1, 1 50, D2 50, and Q1 are adjusted, and a slip increase component is separately added to the negative electrode slurry to prepare the sodium ion batteries of Examples 23 to 26.

[0159] Examples 27 to 29 Based on the preparation method of Example 1, the CW of the negative electrode sheet is adjusted to prepare the sodium ion batteries of Examples 27 to 29.

[0160] Example 30 Based on the preparation method of Example 1, 1 50, D 2 50, and replace the second negative electrode active material particles with microspherical hard carbon particles to prepare a sodium ion battery of Example 30.

[0161] Example 31 Based on the preparation method of Example 1, 1 50, D 2 50, and the first negative electrode active material particles and the second negative electrode active material particles are both replaced with microspherical hard carbon particles to prepare the sodium ion battery of Example 31.

[0162] Example 32 Based on the preparation method of Example 1, 1 50, D 2 50, and replace the first negative electrode active material particles with microspherical hard carbon particles to prepare a sodium ion battery of Example 32.

[0163] Example 33 Based on the preparation method of Example 1, 1 50, D 2 50, and replace the second negative electrode active material particles with soft carbon particles having irregular shapes to prepare a sodium ion battery of Example 33.

[0164] Example 34 Based on the preparation method of Example 1, 1 50, D 250 and replace the second negative electrode active material particles with MCMB particles which are similar to spheres to prepare a sodium ion battery of Example 34.

[0165] Example 35 Based on the preparation method of Example 1, 1 50, D 2 50, and replace the first negative electrode active material particles with soft carbon particles having irregular shapes to prepare a sodium ion battery of Example 35.

[0166] Example 36 Based on the preparation method of Example 1, 1 50, D 2 50, and replace the first negative electrode active material particles with MCMB particles that are similar to spheres to prepare a sodium ion battery of Example 36.

[0167] Examples 37 to 41 Based on the preparation method of Example 1, 1 50, D 2 50, and the type of adhesive used in the negative electrode sheet are adjusted to prepare sodium ion batteries of Examples 37 to 41. Here, the adhesive used in the negative electrode sheet of Example 37 is styrene butadiene rubber (SBR), the adhesive used in the negative electrode sheet of Example 38 is hydrogenated nitrile rubber, the adhesive used in the negative electrode sheet of Example 39 is a copolymer of vinylidene fluoride and hexafluoropropylene, the adhesive used in the negative electrode sheet of Example 40 is a copolymer of vinylidene fluoride and acrylic esters, and the adhesive used in the negative electrode sheet of Example 41 is polytetrafluoroethylene.

[0168] Examples 42 to 45 Based on the preparation method of Example 1, 1 50, D 2 50, and the tap density of the first negative electrode active material particles are adjusted to prepare the sodium ion batteries of Examples 32 to 45.

[0169] Comparative Example 1 According to the preparation method of Example 1, the negative electrode active material particles are replaced with hard carbon particles having an irregular shape and a median diameter of 5 μm to prepare a sodium ion battery of Comparative Example 1.

[0170] Comparative Example 2 According to the preparation method of Example 1, the negative electrode active material particles are replaced with microspherical hard carbon particles with a median diameter of 5 μm to prepare a sodium ion battery of Comparative Example 2.

[0171] Comparative Example 3 Based on the preparation method of Example 1, 1 50, D 2 50 to prepare a sodium ion battery of Comparative Example 3.

[0172] The relevant preparation parameters of the negative electrode sheets of the above Examples 1 to 45 and Comparative Examples 1 to 3 are shown in Table 1 below. Here, Q1 indicates the mass ratio of the first negative electrode active material particles to the total mass of the negative electrode active material particles, Q2 indicates the mass ratio of the second negative electrode active material particles to the total mass of the negative electrode active material particles, and Q3 indicates the mass ratio of the slip-increasing component to the negative electrode active material particles. The tap density ρ, D of the first negative electrode active material particles 1 50, D 2 50 can be tested according to the methods described herein, and d, PA can be calculated according to the methods described herein.

[0173] The relevant test parameters of the negative electrode sheets of Examples 1 to 45 and Comparative Examples 1 to 3 are shown in Table 2 below, where CW, d2, E, and PD can be tested according to the methods described herein, and P can be calculated according to the methods described herein.

[0174] The negative electrode sheet of Example 1 was subjected to an SEM test, and the resulting SEM image is shown in FIG.

[0175] Preparation parameters of negative electrode sheets in Examples 1 to 45 and Comparative Examples 1 to 3 [Table 1]

[0176] Test parameters of negative electrode sheets of Examples 1 to 45 and Comparative Examples 1 to 3 [Table 2]

[0177] In addition, performance tests were conducted on the sodium ion batteries obtained in the above Examples 1 to 45 and Comparative Examples 1 to 3. The test results are shown in Table 3 below.

[0178] (1) Energy density test At 25°C, charge with a constant current of 0.33C until the voltage reaches 4.2V, then charge with a constant voltage of 0.05C at 4.2V, at which point the secondary battery reaches a fully charged state, after which it is left to rest for 5 minutes, discharge with a constant current of 0.33C until the voltage reaches 2.5V, and then leave it to rest for another 5 minutes. The capacity and voltage platform when the secondary battery is discharged with a constant current of 0.5C are recorded, and finally the mass of the secondary battery is measured.

[0179] Energy density of secondary battery (Wh / kg) = (Capacity when secondary battery is discharged at a constant current of 0.33C × Voltage platform when secondary battery is discharged at a constant current of 0.33C) / Mass of secondary battery.

[0180] (2) (Cycle life test) At 25°C, the secondary battery was charged at a constant current of 1 / 3C to 4.2V, then charged at a constant voltage of 4.2V until the current reached 0.05C, left for 5 minutes, and discharged at 1 / 3C to 2.8V. The resulting capacity was designated as the initial capacity C0. The above steps were repeated for the same battery, and the discharge capacity C of the battery after the nth cycle was also recorded. n When recording the battery capacity retention rate P after each cycle n =C n / C0*100%, P n The minimum n value corresponding to the case of ≦80% is taken as the cycle life of the secondary battery.

[0181] Performance test results for Examples 1 to 45 and Comparative Examples 1 to 3 [Table 3]

[0182] To summarize Examples 1 to 6, when the median diameter of the first negative electrode active material particles does not change, as the median diameter of the second negative electrode active material particles becomes smaller, the difference in median diameter between the first negative electrode active material particles and the second negative electrode active material particles becomes larger, and the bulk density of the negative electrode active material particles also becomes larger accordingly. As shown in FIG. 8, the second negative electrode active material particles having a small median diameter can be filled into the gaps between the first negative electrode active material particles, and thus the negative electrode film layer can have a high degree of compaction. To summarize Examples 7 to 11, when the median diameter of the second negative electrode active material particles does not change, as the median diameter of the first negative electrode active material particles becomes larger, the difference in median diameter between the first negative electrode active material particles and the second negative electrode active material particles becomes larger, and thus the bulk density of the negative electrode active material particles also becomes larger accordingly. As a result, the negative electrode film layer can also have a high degree of compaction. Summarizing Examples 4, 10, 12 to 13 and Examples 1, 7, 14, and 19, it can be seen that when the difference between the median diameter of the first negative electrode active material particles and the median diameter of the second negative electrode active material particles is constant, the median diameters of the first negative electrode active material particles and the second negative electrode active material particles all have a certain effect on the compaction degree of the negative electrode film layer. Summarizing Examples 1 to 14 and 19, it can be seen that when the difference between the median diameters of the first negative electrode active material particles and the second negative electrode active material particles is within the range of the present application, the compaction degree of the negative electrode film layer can be effectively improved in all cases, and the parameter P of the negative electrode film layer can be maintained within an appropriate range. This can improve the energy density and cycle life of the sodium ion battery.

[0183] To summarize Examples 15 to 22, it can be seen that the compaction degree of the negative electrode film layer tends to increase and then decrease with the decrease in the mass percentage content Q1 of the first negative electrode active material particles. This is because when Q1 is high, the mass percentage content Q2 of the second negative electrode active material is relatively low, there is a limit to the improvement of the bulk density after mixing, and there is a limit to the increase in the compaction degree after cold pressing, so the compaction degree of the negative electrode film layer is low. When Q1 is low, Q2 is relatively high, and after the second negative electrode active material particles are filled into the voids of the first negative electrode active material particles, there are excess second negative electrode active material particles. Even when cold pressed, the compaction degree of the second negative electrode active material particles in this part is difficult to increase, and the median diameter of the second negative electrode active material particles is small, so the compaction degree of the negative electrode film layer is low. When the contents of Q1 and Q2 are within an appropriate range, the compaction degree of the negative electrode film layer can be effectively improved, and the parameter P corresponding to the negative electrode film layer can be maintained within an appropriate range, so that the sodium ion battery can have both high energy density and long cycle life.

[0184] Summarizing Examples 19, 23 to 26, it can be seen that the compaction degree of the negative electrode film layer can be further improved when a slip increase component is added to the negative electrode slurry. This is because the slip increase component can exert a slipping effect during the cold pressing process of the negative electrode sheet, so that the second negative electrode active material particles are more fully filled into the gaps between the first negative electrode active material particles. Summarizing Examples 23 and 26, it can be seen that the tap density of the negative electrode film layer increases with an increase in the amount of the slip increase component added, but the difference in the energy density of the sodium ion battery is not large. This is because sodium ions are difficult to insert into the slip increase component itself, and the slip increase component improves the compaction degree of the negative electrode film layer while at the same time reducing the theoretical capacity per gram of the negative electrode film layer.

[0185] Summarizing Examples 19, 27 to 29, it can be seen that the one-sided coating weight of the negative electrode film layer does not have much effect on the compaction degree of the negative electrode film layer. When the difference in median size between the first negative electrode active material particles and the second negative electrode active material particles is within the range of this application, the negative electrode film layers having different one-sided coating weights all have high compaction degree, appropriate parameter P, and long cycle life.

[0186] To summarize Examples 19 and 30 to 32, it can be seen that when at least one of the first negative electrode active material particles and the second active material particles is microspherical hard carbon particles, the compaction degree of the negative electrode film layer can be further improved.

[0187] Taking Examples 33 to 36 together, it can be seen that, compared with the soft carbon and MCMB, the hard carbon has a higher theoretical capacity per gram and cycle stability for a sodium ion battery.

[0188] To summarize Examples 19, 37 to 41, compared with the ordinary negative electrode adhesive SBR, the flexible adhesive can improve the compaction degree of the negative electrode membrane layer, improve the long-term cycle performance of the sodium ion battery, and improve the energy density and cycle life of the sodium ion battery.

[0189] To summarize Examples 19 and 42 to 45, it is found that as the tap density of the first negative electrode active material particles increases, the compaction degree of the negative electrode film layer also increases.

[0190] In contrast, in Comparative Examples 1 and 2, only hard carbon particles with a median diameter of 5 μm were used as the negative electrode active material particles, and the compaction degree of the negative electrode film layer was low. As a result, the negative electrode sheet not only has a low energy density, but also has a long electron and sodium ion transmission path, so that the energy density and cycle life of the sodium ion battery are low. In Comparative Example 3, negative electrode active material particles with different median diameters were used for preparation, but in Comparative Example 3, the difference in median diameter between the first negative electrode active material particles and the second negative electrode active material particles was lower than the range specified in the present application, and there was a limit to improving the compaction degree of the negative electrode film layer. Therefore, the sodium ion battery of Comparative Example 3 also has poor energy density and cycle life.

[0191] The present application is not limited to the above-mentioned embodiment. The above-mentioned embodiment is merely an example, and any embodiment having substantially the same configuration as the technical idea in the technical solution of the present application and having similar effects is included in the technical scope of the present application. In addition, various modifications that a person skilled in the art can conceive of to the embodiment can be implemented within the scope of the present application without departing from the spirit of the present application, and other forms constructed by combining some of the components in the embodiment are also included in the scope of the present application.

Claims

1. A negative electrode current collector; a negative electrode film layer located on at least one surface of the negative electrode current collector, the negative electrode film layer including first negative electrode active material particles and second negative electrode active material particles, the first negative electrode active material particles including a plurality of adsorption holes, and the first negative electrode active material particles having a tap density of 0.4 g / cm 3 ~1.4g / cm 3 and optionally 0.6 g / cm 3 ~1.0 g / cm 3 and a negative electrode film layer, a difference d between the median diameters of the first negative electrode active material particles and the second negative electrode active material particles satisfies 3 μm≦d≦19 μm; The compaction density PD of the negative electrode film layer is 0.8 g / cm 3 ≦PD≦1.4g / cm 3 , selectable, 1.0 g / cm 3 ≦PD≦1.2g / cm 3 Meet the negative electrode sheet.

2. The median diameter D of the first negative electrode active material particles 1 50 is between 4 μm and 50 μm, optionally between 4 μm and 25 μm; The median diameter D of the second negative electrode active material particles 2 50 is 1 μm to 40 μm, optionally 1 μm to 20 μm.

3. 3. The negative electrode sheet according to claim 1, wherein the mass percentage content of the first negative electrode active material particles is 5% to 95%, and optionally 70% to 95%, relative to the total mass of the first negative electrode active material particles and the second negative electrode active material particles.

4. The negative electrode sheet according to claim 1 , wherein the elongation percentage E of the negative electrode sheet satisfies 0.1%≦E≦0.2%, and optionally 0.1%≦E≦0.15%.

5. The coating weight CW of the negative electrode film layer on one side is 2 mg / cm 2 ~13mg / cm 2 and optionally 5 mg / cm 2 ~12mg / cm 2 The negative electrode sheet according to claim 1 ,

6. The negative electrode film layer satisfies 30%≦P≦60%, optionally 45%≦P≦55%, Here, P = [1-CW / (d 1 *PA)]*100%, d 1 = d 2 / (1+E), CW represents the coating weight of one side of the negative electrode film layer, PA represents the true density of the negative electrode film layer on one side, E represents the elongation of the negative electrode sheet, and d 2 The negative electrode sheet according to claim 1 , wherein m represents a thickness of the negative electrode film layer on one side.

7. The negative electrode sheet according to claim 1 , wherein the first negative electrode active material particles satisfy at least one of the following: (1) The pore size of the adsorption holes is 0.1 nm to 16 nm, and optionally 1 nm to 7 nm. (2) The specific surface area of ​​the first negative electrode active material particles is 1 m 3 / g to 40m 3 / g, and optionally 1.5m 3 / g-10m 3 / g. (3) The spacing of the (002) plane of the first negative electrode active material particles is 0.34 nm to 0.45 nm, and optionally 0.35 nm to 0.4 nm. (4) The true density of the first negative electrode active material particles is 1.3 g / cm 3 ~2.0g / cm 3 and optionally 1.4 g / cm 3 ~1.8g / cm 3 It is.

8. 8. The negative electrode sheet according to claim 1, wherein the first negative electrode active material particles are one or more types selected from hard carbon, soft carbon, and mesocarbon microbeads, and the second negative electrode active material particles are one or more types selected from hard carbon, soft carbon, and mesocarbon microbeads.

9. the first negative electrode active material particles have an irregular shape and / or a microspherical shape, and the second negative electrode active material particles have an irregular shape and / or a microspherical shape; 9. The negative electrode sheet according to claim 1, wherein the mass percentage content of the first negative electrode active material particles having an irregular shape is 5% to 95%, and optionally 70% to 95%, relative to the total mass of the first negative electrode active material particles and the second negative electrode active material particles.

10. 9. The negative electrode sheet according to claim 1, wherein the first negative electrode active material particles are selected from irregularly shaped hard carbon particles, and the second negative electrode active material particles are selected from microspherical hard carbon particles, and a mass percentage content of the first negative electrode active material particles is 70% to 95% relative to a total mass of the first negative electrode active material particles and the second negative electrode active material particles.

11. The first negative electrode active material particles are selected from microspherical hard carbon particles, and the median diameter D of the first negative electrode active material particles is 1 50 is 10 μm to 50 μm, The second negative electrode active material particles are selected from microspherical hard carbon particles, and the median diameter D of the second negative electrode active material particles is 2 50 is 5 μm to 40 μm, The negative electrode sheet according to any one of claims 1 to 8, wherein the mass percentage content of the first negative electrode active material particles is 5% to 95%, and optionally 70% to 95%, relative to the total mass of the first negative electrode active material particles and the second negative electrode active material particles;

12. The compaction density PD of the negative electrode film layer is 1.0 g / cm 3 ≦PD≦1.2g / cm 3 Fulfilling The negative electrode film layer satisfies 30%≦P≦60%, optionally 45%≦P≦55%, Here, P = [1-CW / (d 1 *PA)]*100%, d 1 = d 2 / (1+E), CW represents the coating weight of one side of the negative electrode film layer, PA represents the true density of the negative electrode film layer on one side, E represents the elongation of the negative electrode sheet, and d 2 The negative electrode sheet according to claim 10 or 11, wherein indicates a thickness of the negative electrode film layer on one side.

13. The negative electrode film layer further comprises a slip-increasing component, and a ratio of the mass of the slip-increasing component to the sum of the mass of the first negative electrode active material particles and the mass of the second negative electrode active material particles is 100:2 to 100:1, and the slip-increasing component comprises one or more of artificial graphite, natural graphite, and graphene. The negative electrode sheet according to claim 10 or 11.

14. 14. The negative electrode sheet according to claim 1, wherein the negative electrode film layer further comprises a flexible adhesive, the flexible adhesive comprising one or more of a styrene acrylic emulsion, a copolymer of vinylidene fluoride and tetrafluoroethylene, a copolymer of vinylidene fluoride and hexafluoropropylene, a copolymer of vinylidene fluoride and acrylic esters, polytetrafluoroethylene, nitrile rubber, and hydrogenated nitrile rubber.

15. A secondary battery comprising the negative electrode sheet according to any one of claims 1 to 14.

16. A battery module comprising the secondary battery according to claim 15.

17. A battery pack comprising the battery module according to claim 16.

18. A power consuming device comprising at least one selected from the group consisting of the secondary battery according to claim 15, the battery module according to claim 16, and the battery pack according to claim 17.

Citation Information

Patent Citations

  • Negative electrode material for nonaqueous electrolyte secondary battery and nonaqueous electrolyte battery using the same

    JP2010251315A